COMPARISON OF VALUE ORIENTATIONS OF STUDENTS IN THE 10YEAR TIME INTERVAL: METHODOLOGY AND RESULTS - Galina I. Saganenko; Alexey E. Geger (Высшее образование в России)
Abstract. The article presents the results of the survey aimed at the identification of human values of students at two time points – 2005 and 2015. In both studies, the values of the students were identified by a reflective method, in which the respondents themselves called their values, clarified their personal sense, and then estimated them quantitatively (by 100 points). We assessed the personal significance of each of value and satisfaction with the state of the respective sphere in their lives. The objective of this study was to carry out two mutually supplementary tasks: (a) to identify the content of personal values and their quantitative assessments, changes for the 10Nyear interval, and (b) to draw attention to the methodological problems, concerning the close relationship between the meaningful results and methodological techniques. The authors point to the prevalence in the value structure of both student groups of the values of private life and the weak expression of humanities and social values, such as patriotism, freedom and democracy, environmental concerns and nature protection.